Gambaran Kesehatan Mental Ibu Hamil di Puskesmas Pangkajene - Sartika, Nurul Hikmah, Andi Sani (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2021)
The COVID-19 pandemic has not only caused a public health crisis but also social, demographic and economic as well as psychosocial effects. Anxiety caused during pregnancy has a negative impact on pregnancy, such as increasing the risk of preeclampsia, depression, nausea, vomiting and even causing premature labor or negative miscarriage, including pregnant women. The purpose of this study was to determine the mental health picture of pregnant women during the covid 19 pandemic. This study is a quantitative study with a descriptive approach. The population is pregnant women who come to visit for antenatal care activities. The number of samples in this study was 117 pregnant women obtained using the Lameshow formula. the source of data is primary data from interviews using questionnaires while secondary data from MCH data at puskesmas, health offices and related journals. The results of this study found that the description of mental health disorders that occurred in Pangkajene Health Center was 35 people suffering from depression (29.9%), anxiety as many as 52 (44.4%) and stress as many as 21 people (17.1%). It is expected that the officers at the community health service center, namely midwives, doctors and nurses, will not only carry out physical examinations but also provide counseling services for pregnant women who have mental health disorders.